Imagem corporal e mudanças físicas relacionadas ao envelhecimento: um estudo de caso - Schiavo, Jaíne Cristo (2018)
INTRODUCTION: The body image is understood as the mental representation of the existential body. Most corporate image studies address the following topics: investigate image satisfaction, repercussions for physical changes such as puberty or gestation and in cases of eating disorders when changes in body image occur. There are few studies about body image in old age involving physical asjica resulting from the aging process and its repercussions. There are studies that address issues involving satisfaction and difficulties from the corporate changes of old age. OBJECTIVES: To discuss the body image related to the aging process from a case study to understand aspects of life history that contribute to coping with the physical changes of this phase of life. METHODS: This is a descriptive and exploratory qualitative study that used the content analysis method to understand the interview data provided. As an instrument, the timeline was used as a means to make the interview more organized and to facilitate the recording and filtering of the most relevant information involving the chronology of life and important aspects of the relationship with the body. Individual interviews were conducted with 6 elderly individuals aged 63-85 years, selecting only one case that met the inclusion criteria of this study. RESULTS: The elderly participant in the study was 74 years old. He presented as characteristic of concern with the appearance, the high stature in the youth. Weight gain, wrinkles and white hair as concerns related to appearance in old age. As for functionality, the practice of physical activities was used as resources to cope with emotional and physical difficulties throughout life and in old age, and sexual activity favored positive relation with the body in both functionality and appearance. CONCLUSION: The coping of the body changes resulting from aging consists in accepting the characteristics of old age, both of appearance and functionality, but one can not lose sight of the fact that each subject suffers differently the emotional impact with the arrival of old age, making it important to understand that adaptation and subjective resources that promote well-being in relation to the body can be alternatives that minimize the difficulties experienced as the body changes with the arrival of aging. In addition, investments that promote lifelong satisfaction with the body as well as social insertion have shown to be relevant aspects to favor a more positive body image in this stage of life